Aflatoxin and Ochratoxin A Contamination in Corn Grains and Sago (Putak Meal) from Different Sources for Poultry in West Timor, Indonesia - Nalle , Catootjie L.; Angi, A.H.; Supit, M.A.J.; Ambarwati, S. (International Journal of Poultry Science, 2019)
Objectives: The main objective of the present study was to evaluate Aflatoxins (B1, B2, G1 and G2) and Ochratoxin A contamination in corn grains and sago (putak meal) in some areas of West Timor, Indonesia. However, because information regarding antinutritional factors in sago is limited, our other objective was to evaluate the content of neutral detergent fiber (NDF), phytic acid and tannins in sago. Materials and Methods: A total of 30 corn samples and whole putak samples from four different sources were collected from traditional markets, farmers and feed mills in Kupang, South Central Timor (SCT), Belu and Malaka regencies in West Timor, Indonesia. Aflatoxins and Ochratoxins were measured using Thin Layer Chromatography (TLC). Results: The results showed that the percentage of sago (putak meal) contaminated with Aflatoxins (B1, B2, B3 and B4) was 0% but that contamination with Ochratoxins was 50% and the amount was 20.385 μg kg–1. Corn grains from farmers and traditional markets in Kupang regency were not found to be contaminated with Aflatoxins (B1, B2, B3 and B4) or Ochratoxin A (OTA); only one corn sample from feed mills was contaminated with Aflatoxin B1 (12.18 μg kg–1). In SCT regency, among the 8 samples analyzed (from traditional markets and farmers), only one sample from a farmer was contaminated with Aflatoxin B1 (24.35 μg kg–1). Corn samples obtained from traditional markets and farmers in the Belu and Malaka regencies were contaminated with Aflatoxin B1 (AFB1) at a concentration of 65.50 and 24.36 μg kg–1, respectively. Conclusion: In conclusion, all Sago (putak meal) was found to be free from Aflatoxins but 50% was contaminated by Ochratoxin A. The majority of corn samples obtained from traditional markets and farmers in West Timor were free from Aflatoxin and Ochratoxin A contamination. The contamination of Ochratoxin A in sago and Aflatoxin B1 in corn samples taken from traditional markets, farmers and feed mills in West Timor was probably a result of improper storage and natural contamination. Huma and metal drums could maintain the quality of the corn samples.